Avaliação do Programa Esporte e Lazer da Cidade no convênio de Recife - Aniele Fernanda Silva de Assis (2017)
The City Sports and Leisure Program, bounded by the Ministry of Sports, coordinated by the National Secretary of Sports, Education, Leisure and Social Inclusion, aims to democratize the access to sports and leisure practices including all age groups through the implementation of recreational sports and leisure centers through agreements signed between municipal, state, district and higher education institutions. Within these centers, thematic workshops were planned and carried out. The educational actions were developed from the perspective of human emancipation and community development and they were guided by pedagogical guidelines. In order to verify if the objectives and the guidelines of the program were materialized in their political, pedagogical and technical aspects, Recife was chosen as a covenant to be evaluated. For this purpose, the general objective of this thesis is to evaluate how the objectives and the guidelines of the PELC materialize in the agreement of Recife within the political, pedagogical and technical aspects. Some specific objectives are: to analyze the limits and potentialities pointed out by the individuals to the materialization of the objectives and the guidelines of the PELC; Evaluate the relationship between local and federal policies viewing the continuity of the program from a municipal perspective; Understand how the daily activities of the PELC, workshops-events-training, are held in the covenant of Recife; Identify the motivations for the access and permanence of the participants. To accomplish this research, a combination of procedures and techniques was necessary. Bibliographical research was used to investigate the academic productions that concern with the evaluation of sports and leisure public policies and the PELC; Documentary research with the various documents guiding local and national policies; Field research in four PELC centers in Recife: Brasília Teimosa / Pina, Campo Grande / Chié, Geraldão and Santo Amaro / Ilha de Santa Terezinha. In the field research, observations were made in the center. Also, semi-structured interviews with local managers were done (the Sports Executive Secretary and the president of Geraldo Magalhães Sports Gymnasium Geraldão) as well as emphasis in groups such as participant population, social agents and general/pedagogical coordinators. To perform the interpretations and analysis of the data, an analysis of content by subject matter was done through the categories of organization of pedagogical work, management, training and professional valorization. The triangulation of the data identified that the PELC in Recife has taken important steps in its realization: it democratized sports and leisure actions, created and strengthened the bond between subjects and institutions and furthermore, it mobilized the community for self-organization provoking the subjects regarding the diversity. Considering Recife's historical trajectory in the development of public sports and leisure policies, it is time to consolidate it as a state policy, using protagonism, political formation, community mobilization and results already achieved to advance the process of municipalization. The democratic and popular participation of the various individuals involved in the political process can aide in the transformation of reality, envisioning a scenario conducive to experiencing the various cultural practices of sports and leisure